Global prevalence and determinants associated with the acceptance of monkeypox vaccination - Indiastari, Dewi; Fajar, Jonny K.; Tamara, Fredo; Runesi, Odis; Hakim, Lukman N.; Chotimah, Kusnul; Rahmani, Alinda; Saputro, Teguh D.; Afrilla, Dian; Firmansyah, Ervin; Dau, Daniel; Dzhyvak, Volodymyr (Narra J, 2024)
Assessing the acceptance of the monkeypox vaccine is crucial for the success of vaccination programs, yet the prevalence reports remain inconclusive. The aim of this study was to determine the global prevalence of monkeypox vaccine acceptance and identify its associated factors. A meta-analysis was conducted with a comprehensive search strategy on the following databases, including Scopus, Embase, and PubMed, for articles published up to April 5, 2024. This study utilizes a single-arm meta-analysis to calculate the pooled prevalence of monkeypox vaccine acceptance. A Z-test was employed to identify factors associated with the vaccine acceptance. Our study analyzed 51 articles encompassing 98,746 participants, revealing an overall monkeypox vaccine acceptance rate of 65%. Notably, the highest acceptance rates were observed among men who have sex with men (MSMs), while healthcare workers (HCWs) showed the lowest acceptance rates. Additionally, our findings indicated an increased acceptance in individuals with educational attainment beyond a bachelor’s degree, a history of COVID-19 and influenza vaccination, homosexual orientation, and HIV-positive status. Conversely, lower acceptance risk was associated with those with educational attainment below a bachelor's degree, heterosexual orientation, and bisexual orientation. In conclusion, our current study has determined the rate of monkeypox vaccine acceptance and identified its associated factors. These findings offer valuable insights as the foundation for targeted policies to manage and increase acceptance rates.